Three-dimensional biofilm properties on dental bonding agent with varying quaternary ammonium charge densities - Zhou, Han (J Dent, 2016)
OBJECTIVES: Tooth-restoration interfaces are the weak link with secondary caries causing restoration failure. The objectives of this study were to develop an antimicrobial bonding agent with dimethylaminododecyl methacrylate (DMAHDM), and investigate the effects of quaternary amine charge density on three-dimensional (3D) biofilms on dental resin for the first time. METHODS: DMAHDM was synthesized and incorporated into Scotchbond Multi-Purpose bonding agent at mass fractions of 0% (control), 2.5%, 5%, 7.5% and 10%. Streptococcus mutans bacteria were inoculated on the polymerized resin and cultured for two days to form biofilms. Confocal laser scanning microscopy was used to measure biofilm thickness, live and dead biofilm volumes, and liv bacteria percentage in 3D biofilm vs. distance from resin surface. RESULTS: Charge density of the resin had a significant effect on the antibacterial efficacy (p < 0.05). Biofilms on control resin had the greatest thicknesses. Biofilm thickness and live biofilm volume decreased with increasing surface charge density (p < 0.05). There were significant variations in bacterial viability along the 3D biofilm thickness (p < 0.05). At 2.5% and 5% DMAHDM, the bacterial inhibition was the greatest on or near the resin surface, and the killing effect decreased away from the resin surface. At 10% DMAHDM, the entire 3D biofilm was dead and the percentage of live bacteria was nearly 0% throughout the biofilm thickness. CONCLUSIONS: Adding new antibacterial monomer DMAHDM into dental bonding agent yielded a strong antimicrobial activity, substantially decreasing the 3D biofilm thickness, live biofilm volume, and percentage of live bacteria on cross-sections through the biofilm thickness. SIGNIFICANCE: Novel DMAHDM-containing bonding agent with capability of inhibiting 3D biofilms is promising for a wide range of dental restorative and preventive applications to inhibit biofilms at the tooth-restoration margins and prevent secondary caries.